The Influence of Identity Politics within Families on First-Time Voters in Aceh - Faisal, Naidi; Sofyan, Hizir; M. Syam, Hamdani; Jamil, T. M.; Yunus, Saifuddin (Jurnal Ilmiah Peuradeun, 2025)
This article explores the transmission of identity politics within families and its impact on the attitudes and political choices of first-time voters in Aceh. The significance of this study is emphasized by the electoral periods in Aceh and Indonesia, which are frequently influenced by strong identity politics. The study addresses two main questions: How does family identity influence the political understanding of first-time voters, and how does the transmission of political identity occur within families? Employing a qualitative case study approach, the research collected data through interviews with first-time voters from UIN Ar-Raniry and Universitas Malikussaleh. Findings reveal that in the context of Aceh, political identity, entrenched within family dynamics through political affiliations, religious values, and personal experiences, significantly shapes the political perspectives of first-time voters. Predominantly, the paternal figure acts as the primary agent of socialization, disseminating political orientations through family discussions and daily interactions, often without allowing for critical evaluation. This research confirms that families not only serve as institutions influencing and transmitting political views to first-time voters in Aceh but also restrict their ability to conduct independent political assessments due to the reinforcement of traditional and religious values in this transmission.